Carbon nanofiber loaded cobalt-zinc sulfide composite material, preparation method thereof and modified lithium-sulfur battery diaphragm
By using carbon nanofiber-loaded cobalt-zinc sulfide composite materials on the lithium-sulfur battery separator, the problem of polysulfide diffusion in lithium-sulfur batteries is solved, the electrochemical performance and cycle stability of the battery are improved, and the battery life is extended.
Patent Information
- Application Number
- CN202411388961.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-14
AI Technical Summary
The "shuttle effect" of polysulfides in lithium-sulfur batteries leads to low energy storage efficiency and short life. The traditional diaphragm pore size is a serious problem. It is necessary to develop efficient diaphragm materials to inhibit the diffusion of polysulfides.
Using carbon nanofiber-loaded cobalt-zinc sulfide composite material, a bimetallic CoZn-MOF precursor was grown on the bacterial cellulose network, and CNF/CoZn with excellent conductivity and stability was prepared through one-step sulfidation and carbonization treatment. S material, as a coating for the modified lithium sulfur battery separator, to limit the diffusion of polysulfides.
It effectively alleviates the "shuttle effect" of polysulfide, improves the electrochemical performance and cycle stability of lithium-sulfur batteries, improves the specific capacity and rate performance of the battery, and extends the battery life.
Smart Images

Figure CN119306208A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional materials, and in particular is a carbon nanofiber-loaded cobalt-zinc sulfide composite material and a preparation method thereof, and a modified lithium-sulfur battery separator. Background Art
[0002] There are many upgrades and changes in energy storage systems, such as batteries, capacitors, and physical water storage. Since the successful launch of lithium intercalation electrochemistry in the 1990s, lithium-ion batteries (LIBs) have dominated the battery market for portable electronic devices. The highest energy density of lithium-ion batteries is approaching its limit, but it still cannot meet the needs of emerging electric vehicles, hybrid vehicles, and next-generation portable electronic devices. As a new type of high-energy storage device, lithium-sulfur batteries have a theoretical capacity of up to 1675mAh·g -1 , the theoretical mass energy density is as high as 2600Wh / kg. Moreover, as the positive electrode of the battery, elemental sulfur has the advantages of abundant reserves, low cost, environmental friendliness, safety and reliability. Therefore, lithium-sulfur batteries are considered to be the next generation of battery energy storage devices with great application prospects, which has attracted widespread attention from scientific researchers. However, the development of lithium-sulfur batteries still has bottleneck problems that need to be solved urgently. The poor conductivity of positive electrode sulfur, the volume change of the electrode during charging and discharging, and the "shuttle effect" of polysulfides seriously reduce the energy storage efficiency of the battery and shorten the battery life. Among them, the most serious and urgent problem to be solved is the "shuttle effect" of polysulfides. The elemental sulfur positive electrode forms soluble polysulfide intermediates during the charging and discharging process. The polysulfides diffuse in the electrolyte to the lithium negative electrode and continuously deposit on the surface of the lithium negative electrode, thereby increasing the internal impedance of the battery and sharply reducing the electrochemical performance. Therefore, inhibiting the "shuttle effect" of polysulfides has become the key to improving the comprehensive performance of current Li-S batteries.
[0003] As a key component of lithium-sulfur batteries, diaphragm materials play an important role in the overall performance of the battery. Although the diaphragm does not directly participate in any battery reaction, its structure and properties play an important role in determining battery performance, including cycle life, safety and energy density, by affecting battery dynamics. Traditional lithium-sulfur batteries widely use commercial polyolefin diaphragms (PP, PE or PP / PE), which have relatively large pore sizes, resulting in polysulfides easily shuttling to the negative electrode. Therefore, it is necessary to modify a layer of functional material on the diaphragm to effectively inhibit the "shuttle effect" of polysulfides, thereby improving the cycle stability of lithium-sulfur batteries.
[0004] Metal-Organic Frameworks (MOFs) are functional materials that have been widely studied in recent years. Compared with traditional inorganic porous materials, MOFs have the advantages of high porosity, high specific surface area, modifiable chemical properties and catalytic properties of the central metal. Moreover, MOFs have natural advantages in building structures, which are conducive to the further conversion of their uniformly distributed metal centers and organic ligands into metal compounds and carbon skeletons through a simple pyrolysis process. In addition, ZIF-67 and its derived cobalt-containing compounds such as cobalt sulfide, cobalt nitride and cobalt phosphide are polar compounds, which have chemical adsorption and catalytic effects on polysulfides and can effectively limit the "shuttle effect" of polysulfides. For example, [J.He, Y.Chen, A.Manthiram.Vertical Co9S8 hollow nanowall arrays grown on a Celgard separator as a multifunctional polysulfide barrier for high-performance Li-S batteries[J].Energy Environ. Sci., 2018, 11(9): 2560-2568.] reported a simple and feasible in-situ liquid growth reaction method to grow a layer of Co-MOF-derived Co9S8 nanoarrays with vertical hollow nanostructures on a Celgard membrane, which served as an effective barrier to limit the "shuttle effect" of polysulfides in Li-S batteries and exhibited excellent electrochemical performance. However, as nanomaterials, traditional MOF materials and their derivatives will agglomerate during the preparation and application process, which greatly reduces their natural advantages and has low conductivity. Therefore, the composite of MOF and its derivatives with carbon materials has become a new research direction in the field of Li-S batteries.
[0005] Bacterial cellulose (BC) is a carbon material with a unique natural 3D ultrafine nanofiber network structure. It has a large specific surface area and high porosity, thus having good electrolyte absorption capacity and reducing interface resistance. BC has excellent mechanical properties and can maintain a three-dimensional network structure to a large extent after high-temperature treatment. The 3D carbon nanofiber (CNF) separator can improve lithium ion transmission through its conductive skeleton and can effectively alleviate the "shuttle effect" of polysulfides. In addition, BC is rich in hydroxyl functional groups, which enables MOF and its derivatives to grow in situ on its surface, which can effectively alleviate the agglomeration problem of MOF and its derivative particles.
[0006] Multiple metal active sites can simultaneously enhance the redox reactions of sulfur and polysulfides with different structures. For example, in [Zhang Ze, Wang Jianan, Shao Ahu, et al. Cobalt-molybdenum bimetallic carbide modified membrane enhances the adsorption and catalytic conversion of lithium polysulfides in lithium-sulfur batteries (English) [J]. Science China Materials, 2020, 63(12): 2443-2455.], a cobalt-molybdenum bimetallic carbide (Co3Mo3C) catalytic material was synthesized for modifying lithium-sulfur battery membranes. Theoretical calculation results show that compared with single metal carbide Mo2C, bimetallic carbide Co3Mo3C has more active sites, which is more conducive to chemical fixation of lithium polysulfides and catalyzes the mutual conversion between lithium polysulfides.
[0007] However, there are few reports on the research of BC / MOF composites in Li-S battery modified membranes. Therefore, it is urgent to develop a BC / MOF-derived bimetallic composite material suitable for Li-S battery membrane modification, which can effectively alleviate the "shuttle effect" of polysulfides, improve the conductivity of the membrane, promote the redox reaction of polysulfides, and improve the utilization efficiency of active substances. Summary of the invention
[0008] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a carbon nanofiber-loaded cobalt-zinc sulfide composite material and a preparation method thereof and a modified lithium-sulfur battery separator. Not only is the preparation method simple and the process short, but the prepared CNF / CoZn-S can effectively alleviate the "shuttle effect" of polysulfides and improve the electrochemical performance of Li-S batteries.
[0009] In order to achieve the above object, the present invention adopts the following technical solutions:
[0010] A method for preparing a carbon nanofiber-loaded cobalt-zinc sulfide composite material comprises the following steps:
[0011] Step 1, mixing bacterial cellulose hydrogel BC with deionized water, stirring evenly, and freeze-drying to obtain BC fibers with a network structure;
[0012] Step 2, firstly mix Co(NO3)2·6H2O and Zn(NO3)2·6H2O in a molar ratio of (1-2):(1-2) to obtain a mixture A, and then dissolve 0.015 mol of the mixture A and 0.1-0.4 g of BC fiber in 50-120 mL of methanol to obtain a mixed solution B;
[0013] Step 3, dissolving 3.08 g of 2-methylimidazole in 50-120 mL of methanol to obtain a mixed solution C;
[0014] Step 4, drop the mixed solution B into the mixed solution C, stir, stand at room temperature, vacuum filter, wash and vacuum dry in sequence to obtain a purple BC / CoZn-MOF precursor;
[0015] Step 5. According to the mass ratio of 1:4, the BC / CoZn-MOF precursor and sulfur powder are placed at both ends of the magnetic boat respectively, and the magnetic boat is placed in a tubular furnace. Under Ar atmosphere, the temperature is first increased from room temperature to 300°C at a heating rate of 5°C / min, and kept warm for 2 to 4 hours. Then, the temperature is increased to 700°C at a heating rate of 2°C / min, and kept warm for 0 to 4 hours. Naturally cool to room temperature to obtain a carbon nanofiber-loaded cobalt zinc sulfide composite material CNF / CoZn-S.
[0016] Furthermore, in step 1, the volume ratio of bacterial cellulose hydrogel BC to deionized water is 1:30, and the solid content of bacterial cellulose hydrogel BC is 0.8%.
[0017] Furthermore, in step 2, the molar ratio of Co(NO3)2·6H2O to Zn(NO3)2·6H2O is 1:1, 2:1 or 1:2.
[0018] Furthermore, in step 2, the molar ratio of Co(NO3)2·6H2O to Zn(NO3)2·6H2O is 1:2.
[0019] Furthermore, the standing time of step 4 is 24 hours.
[0020] Furthermore, the cleaning in step 4 is performed by alternately washing with deionized water and anhydrous ethanol for 3 times.
[0021] Furthermore, the vacuum drying in step 4 is carried out at 60° C. for 12 hours.
[0022] A carbon nanofiber-loaded cobalt zinc sulfide composite material CNF / CoZn-S.
[0023] A modified lithium-sulfur battery separator comprises a commercial polypropylene separator, the surface of which is coated with a carbon nanofiber-loaded cobalt-zinc sulfide composite material CNF / CoZn-S.
[0024] Furthermore, the modified lithium-sulfur battery separator is prepared by the following method:
[0025] CNF / CoZn-S, acetylene black and PVDF were weighed in a mass ratio of 8:1:1, mixed evenly and ground, and NMP was added to prepare a uniform slurry. The slurry was evenly coated on the surface of a commercial polypropylene separator and dried to obtain a modified lithium-sulfur battery separator.
[0026] Compared with the prior art, the present invention has the following technical effects:
[0027] The present invention adjusts the molar ratio of the cobalt source and the zinc source, adopts an in-situ growth method to grow a bimetallic CoZn-MOF on a 3D ultrafine nanofiber network of hydroxylated bacterial cellulose BC rich in functional groups, and prepares a BC / CoZn-MOF composite material. The BC / CoZn-MOF composite material is used as a precursor, and a carbon nanofiber-supported cobalt zinc sulfide composite material CNF / CoZn-S is obtained through a one-step sulfurization and carbonization heat treatment process. The composite material has the advantages of simple preparation process and short production cycle.
[0028] The CNF / CoZn-S prepared by the present invention maintains the ultrafine network structure of BC. As a highly conductive network, the ultrafine network structure not only has excellent conductivity, but also has rich functional groups, which can alleviate the agglomeration and stacking problems of CoZn-MOF, expose more active sites of the composite material, and improve its adsorption effect on polysulfides; at the same time, the bimetallic sulfide CoZn-S uniformly grown on BC has good stability and polarity, and its heterogeneous structure can provide more abundant sulfur vacancies, has a stronger catalytic ability for polysulfides, improves the utilization rate of active substances, can effectively alleviate the "shuttle effect" of polysulfides, and improves the electrochemical performance of the battery; in short, CNF / CoZn-S has the dual characteristics of CNF and cobalt zinc sulfide nanoparticles, has excellent conductivity, and can serve as a physical barrier to limit the shuttling of LiPSs, thereby effectively alleviating the "shuttle effect" of polysulfides in Li-S batteries, and improving the conversion efficiency and cycle stability of Li-S batteries for polysulfides.
[0029] The present invention utilizes a commercial lithium-sulfur battery separator modified by CNF / CoZn-S to give the lithium-sulfur battery better rate performance, cycle performance and higher specific capacity, thereby improving the electrochemical performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 XRD diagrams of CNF / CoZn-S synthesized in Examples 1 to 3 of the present invention, CNF / Co-S synthesized in Comparative Example 1, and CNF / Zn-S synthesized in Comparative Example 2;
[0031] Figure 2 This is a SEM image of BC / CoZn-MOF-1:2 synthesized in Example 2 of the present invention;
[0032] Figure 3 This is the SEM image of CNF / CoZn-S-1:2 synthesized in Example 2 of the present invention;
[0033] Figure 4 The charge and discharge curves of the Li-S battery assembled with the modified diaphragms synthesized in Examples 1 to 3, Comparative Examples 1 and 2 and the commercial diaphragm at a current density of 0.1C are shown in the figure.
[0034] Figure 5 The rate performance of Li-S batteries assembled with modified diaphragms synthesized in Examples 1 to 3, Comparative Examples 1 and 2 and commercial diaphragms of the present invention;
[0035] Figure 6 The Li-S battery assembled with the modified diaphragms synthesized in Examples 1 to 3, Comparative Examples 1 and 2 and the commercial diaphragms of the present invention has a resistance of 0.1 mV·s -1 CV curve under scanning speed;
[0036] Figure 7 The cycle curves of Li-S batteries assembled with modified diaphragms synthesized in Examples 1 to 3, Comparative Examples 1 and 2 and commercial diaphragms of the present invention at a current density of 0.2C are shown;
[0037] Figure 8 The cycle curves of Li-S batteries assembled with the modified diaphragms synthesized in Examples 1 to 3, Comparative Examples 1 and 2 and commercial diaphragms of the present invention at a current density of 1C;
[0038] Fig. 9 The cycle curves of Li-S batteries assembled with the modified diaphragms synthesized in Examples 1 to 3, Comparative Examples 1 and 2 and commercial diaphragms of the present invention at a current density of 2C;
[0039] Fig.10 The EIS curves of Li-S batteries assembled with the modified separators synthesized in Examples 1 to 3, Comparative Examples 1 and 2 and commercial separators of the present invention are shown. DETAILED DESCRIPTION
[0040] The specific contents of the present invention are further explained in detail below in conjunction with embodiments.
[0041] Example 1
[0042] Step 1, mixing bacterial cellulose hydrogel BC with a solid content of 0.8% and deionized water in a volume ratio of 1:30, stirring evenly, and freeze-drying to obtain BC fibers with a network structure;
[0043] Step 2: Mix 0.0075 mol of Co(NO3)2·6H2O and 0.0075 mol of Zn(NO3)2·6H2O to obtain a mixture A, and dissolve the mixture A and 0.15 g of BC fiber in 100 mL of methanol to obtain a mixed solution B;
[0044] Step 3, dissolving 3.08 g of 2-methylimidazole in 100 mL of methanol to obtain a mixed solution C;
[0045] Step 4, drop the mixed solution B into the mixed solution C, stir magnetically for 10 min, stand at room temperature for 24 h, vacuum filter, collect the purple precipitate, then wash it alternately with deionized water and anhydrous ethanol for 3 times, and vacuum dry it at 60 ° C for 12 h to obtain a purple precursor, recorded as BC / CoZn-MOF-1:1;
[0046] Step 5, according to the mass ratio of 1:4, BC / CoZn-MOF-1:1 and sulfur powder are placed at both ends of the magnetic boat respectively, and the magnetic boat is placed in a tube furnace. Under Ar atmosphere, the temperature is first increased from room temperature to 300°C at a heating rate of 5°C / min, and kept warm for 2h, and then increased to 700°C at a heating rate of 2°C / min, and kept warm for 2h, and naturally cooled to room temperature to obtain a carbon nanofiber-supported cobalt zinc sulfide composite material, recorded as CNF / CoZn-S-1:1;
[0047] Step 6. According to the mass ratio of 8:1:1, weigh CNF / CoZn-S-1:1, acetylene black and PVDF, mix and grind them evenly, add 10 drops of N-methylpyrrolidone NMP to prepare a uniform slurry, evenly coat the slurry on the surface of a commercial polypropylene separator, and dry it to obtain a CNF / CoZn-S-1:1 modified lithium-sulfur battery separator.
[0048] Example 2
[0049] Step 1, mixing bacterial cellulose hydrogel BC with a solid content of 0.8% and deionized water in a volume ratio of 1:30, stirring evenly, and freeze-drying to obtain BC fibers with a network structure;
[0050] Step 2: Mix 0.005 mol of Co(NO3)2·6H2O and 0.01 mol of Zn(NO3)2·6H2O to obtain a mixture A, and dissolve the mixture A and 0.15 g of BC fiber in 100 mL of methanol to obtain a mixed solution B;
[0051] Step 3, dissolving 3.08 g of 2-methylimidazole in 100 mL of methanol to obtain a mixed solution C;
[0052] Step 4, drop the mixed solution B into the mixed solution C, stir magnetically for 10 min, stand at room temperature for 24 h, vacuum filter, collect the purple precipitate, then wash it alternately with deionized water and anhydrous ethanol for 3 times, and vacuum dry it at 60 ° C for 12 h to obtain a purple precursor, recorded as BC / CoZn-MOF-1:2;
[0053] Step 5, according to the mass ratio of 1:4, BC / CoZn-MOF-1:2 and sulfur powder are placed at both ends of the magnetic boat respectively, and the magnetic boat is placed in a tube furnace. Under Ar atmosphere, the temperature is first increased from room temperature to 300°C at a heating rate of 5°C / min, and kept warm for 2h, and then increased to 700°C at a heating rate of 2°C / min, and kept warm for 2h, and naturally cooled to room temperature to obtain a carbon nanofiber-supported cobalt zinc sulfide composite material, recorded as CNF / CoZn-S-1:2;
[0054] Step 6. According to the mass ratio of 8:1:1, weigh CNF / CoZn-S-1:2, acetylene black and PVDF, mix and grind them evenly, add 10 drops of N-methylpyrrolidone NMP to prepare a uniform slurry, evenly coat the slurry on the surface of a commercial polypropylene separator, and dry it to obtain a CNF / CoZn-S-1:2 modified lithium-sulfur battery separator.
[0055] Example 3
[0056] Step 1, mixing bacterial cellulose hydrogel BC with a solid content of 0.8% and deionized water in a volume ratio of 1:30, stirring evenly, and freeze-drying to obtain BC fibers with a network structure;
[0057] Step 2: Mix 0.01 mol of Co(NO3)2·6H2O and 0.005 mol of Zn(NO3)2·6H2O to obtain a mixture A, and dissolve the mixture A and 0.15 g of BC fiber in 100 mL of methanol to obtain a mixed solution B;
[0058] Step 3, dissolving 3.08 g of 2-methylimidazole in 100 mL of methanol to obtain a mixed solution C;
[0059] Step 4, drop the mixed solution B into the mixed solution C, stir magnetically for 10 min, stand at room temperature for 24 h, vacuum filter, collect the purple precipitate, then wash it alternately with deionized water and anhydrous ethanol for 3 times, and vacuum dry it at 60 ° C for 12 h to obtain a purple precursor, recorded as BC / CoZn-MOF-2:1;
[0060] Step 5, according to the mass ratio of 1:4, BC / CoZn-MOF-2:1 and sulfur powder are placed at both ends of the magnetic boat respectively, and the magnetic boat is placed in a tube furnace. Under Ar atmosphere, the temperature is first increased from room temperature to 300°C at a heating rate of 5°C / min, and the temperature is kept for 2 hours. Then, the temperature is increased to 700°C at a heating rate of 2°C / min, and the temperature is kept for 2 hours. The carbon nanofiber-supported cobalt zinc sulfide composite material is obtained, which is recorded as CNF / CoZn-S-2:1;
[0061] Step 6. According to the mass ratio of 8:1:1, weigh CNF / CoZn-S-2:1, acetylene black and PVDF, mix and grind them evenly, add 10 drops of N-methylpyrrolidone NMP to prepare a uniform slurry, evenly coat the slurry on the surface of a commercial polypropylene separator, and dry it to obtain a CNF / CoZn-S-2:1 modified lithium-sulfur battery separator.
[0062] Example 4
[0063] Step 1, mixing bacterial cellulose hydrogel BC with a solid content of 0.8% and deionized water in a volume ratio of 1:30, stirring evenly, and freeze-drying to obtain BC fibers with a network structure;
[0064] Step 2: Mix 0.0075 mol of Co(NO3)2·6H2O and 0.0075 mol of Zn(NO3)2·6H2O to obtain a mixture A, and dissolve the mixture A and 0.3 g of BC fiber in 120 mL of methanol to obtain a mixed solution B;
[0065] Step 3, dissolving 3.08 g of 2-methylimidazole in 120 mL of methanol to obtain a mixed solution C;
[0066] Step 4, drop the mixed solution B into the mixed solution C, stir magnetically for 10 min, stand at room temperature for 24 h, vacuum filter, collect the purple precipitate, then wash it alternately with deionized water and anhydrous ethanol for 3 times, and vacuum dry it at 60 ° C for 12 h to obtain a purple precursor, recorded as BC / CoZn-MOF-1:1;
[0067] Step 5, according to the mass ratio of 1:4, BC / CoZn-MOF-1:1 and sulfur powder are placed at both ends of the magnetic boat respectively, and the magnetic boat is placed in a tube furnace. Under Ar atmosphere, the temperature is first increased from room temperature to 300°C at a heating rate of 5°C / min, and kept warm for 4 hours, and then increased to 700°C at a heating rate of 2°C / min, and kept warm for 3 hours, and naturally cooled to room temperature to obtain a carbon nanofiber-supported cobalt zinc sulfide composite material, recorded as CNF / CoZn-S-1:1;
[0068] Step 6. According to the mass ratio of 8:1:1, weigh CNF / CoZn-S-1:1, acetylene black and PVDF, mix and grind them evenly, add 10 drops of N-methylpyrrolidone NMP to prepare a uniform slurry, evenly coat the slurry on the surface of a commercial polypropylene separator, and dry it to obtain a CNF / CoZn-S-1:1 modified lithium-sulfur battery separator.
[0069] Example 5
[0070] Step 1, mixing bacterial cellulose hydrogel BC with a solid content of 0.8% and deionized water in a volume ratio of 1:30, stirring evenly, and freeze-drying to obtain BC fibers with a network structure;
[0071] Step 2: Mix 0.0075 mol of Co(NO3)2·6H2O and 0.0075 mol of Zn(NO3)2·6H2O to obtain a mixture A, and dissolve the mixture A and 0.4 g of BC fiber in 80 mL of methanol to obtain a mixed solution B;
[0072] Step 3, dissolving 3.08 g of 2-methylimidazole in 80 mL of methanol to obtain a mixed solution C;
[0073] Step 4, drop the mixed solution B into the mixed solution C, stir magnetically for 10 min, stand at room temperature for 24 h, vacuum filter, collect the purple precipitate, then wash it alternately with deionized water and anhydrous ethanol for 3 times, and vacuum dry it at 60 ° C for 12 h to obtain a purple precursor, recorded as BC / CoZn-MOF-1:1;
[0074] Step 5, according to the mass ratio of 1:4, BC / CoZn-MOF-1:1 and sulfur powder are placed at both ends of the magnetic boat respectively, and the magnetic boat is placed in a tube furnace. Under Ar atmosphere, the temperature is first increased from room temperature to 300°C at a heating rate of 5°C / min, and the temperature is kept for 3 hours, and then the temperature is increased to 700°C at a heating rate of 2°C / min, and the temperature is kept for 4 hours. The carbon nanofiber-supported cobalt zinc sulfide composite material is obtained, which is recorded as CNF / CoZn-S-1:1;
[0075] Step 6. According to the mass ratio of 8:1:1, weigh CNF / CoZn-S-1:1, acetylene black and PVDF, mix and grind them evenly, add 10 drops of N-methylpyrrolidone NMP to prepare a uniform slurry, evenly coat the slurry on the surface of a commercial polypropylene separator, and dry it to obtain a CNF / CoZn-S-1:1 modified lithium-sulfur battery separator.
[0076] Example 6
[0077] Step 1, mixing bacterial cellulose hydrogel BC with a solid content of 0.8% and deionized water in a volume ratio of 1:30, stirring evenly, and freeze-drying to obtain BC fibers with a network structure;
[0078] Step 2: Mix 0.005 mol of Co(NO3)2·6H2O and 0.01 mol of Zn(NO3)2·6H2O to obtain a mixture A, and dissolve the mixture A and 0.3 g of BC fiber in 110 mL of methanol to obtain a mixed solution B;
[0079] Step 3, dissolving 3.08 g of 2-methylimidazole in 110 mL of methanol to obtain a mixed solution C;
[0080] Step 4, drop the mixed solution B into the mixed solution C, stir magnetically for 10 min, stand at room temperature for 24 h, vacuum filter, collect the purple precipitate, then wash it alternately with deionized water and anhydrous ethanol for 3 times, and vacuum dry it at 60 ° C for 12 h to obtain a purple precursor, recorded as BC / CoZn-MOF-1:2;
[0081] Step 5, according to the mass ratio of 1:4, BC / CoZn-MOF-1:2 and sulfur powder are placed at both ends of the magnetic boat respectively, and the magnetic boat is placed in a tube furnace. Under Ar atmosphere, the temperature is first increased from room temperature to 300°C at a heating rate of 5°C / min, and the temperature is kept for 3 hours, and then the temperature is increased to 700°C at a heating rate of 2°C / min, and the temperature is kept for 1 hour. The carbon nanofiber-supported cobalt zinc sulfide composite material is obtained, which is recorded as CNF / CoZn-S-1:2;
[0082] Step 6. According to the mass ratio of 8:1:1, weigh CNF / CoZn-S-1:2, acetylene black and PVDF, mix and grind them evenly, add 10 drops of N-methylpyrrolidone NMP to prepare a uniform slurry, evenly coat the slurry on the surface of a commercial polypropylene separator, and dry it to obtain a CNF / CoZn-S-1:2 modified lithium-sulfur battery separator.
[0083] Example 7
[0084] Step 1, mixing bacterial cellulose hydrogel BC with a solid content of 0.8% and deionized water in a volume ratio of 1:30, stirring evenly, and freeze-drying to obtain BC fibers with a network structure;
[0085] Step 2: Mix 0.005 mol of Co(NO3)2·6H2O and 0.01 mol of Zn(NO3)2·6H2O to obtain a mixture A, and dissolve the mixture A and 0.25 g of BC fiber in 70 mL of methanol to obtain a mixed solution B;
[0086] Step 3, dissolving 3.08 g of 2-methylimidazole in 70 mL of methanol to obtain a mixed solution C;
[0087] Step 4, drop the mixed solution B into the mixed solution C, stir magnetically for 10 min, stand at room temperature for 24 h, vacuum filter, collect the purple precipitate, then wash it alternately with deionized water and anhydrous ethanol for 3 times, and vacuum dry it at 60 ° C for 12 h to obtain a purple precursor, recorded as BC / CoZn-MOF-1:2;
[0088] Step 5, according to the mass ratio of 1:4, BC / CoZn-MOF-1:2 and sulfur powder are placed at both ends of the magnetic boat respectively, and the magnetic boat is placed in a tube furnace. Under Ar atmosphere, the temperature is first increased from room temperature to 300°C at a heating rate of 5°C / min, and the temperature is kept for 3 hours, and then the temperature is increased to 700°C at a heating rate of 2°C / min, and the temperature is kept for 4 hours. The carbon nanofiber-supported cobalt zinc sulfide composite material is obtained, which is recorded as CNF / CoZn-S-1:2;
[0089] Step 6. According to the mass ratio of 8:1:1, weigh CNF / CoZn-S-1:2, acetylene black and PVDF, mix and grind them evenly, add 10 drops of N-methylpyrrolidone NMP to prepare a uniform slurry, evenly coat the slurry on the surface of a commercial polypropylene separator, and dry it to obtain a CNF / CoZn-S-1:2 modified lithium-sulfur battery separator.
[0090] Example 8
[0091] Step 1, mixing bacterial cellulose hydrogel BC with a solid content of 0.8% and deionized water in a volume ratio of 1:30, stirring evenly, and freeze-drying to obtain BC fibers with a network structure;
[0092] Step 2: Mix 0.01 mol of Co(NO3)2·6H2O and 0.005 mol of Zn(NO3)2·6H2O to obtain a mixture A, and dissolve the mixture A and 0.2 g of BC fiber in 50 mL of methanol to obtain a mixed solution B;
[0093] Step 3, dissolving 3.08 g of 2-methylimidazole in 50 mL of methanol to obtain a mixed solution C;
[0094] Step 4, drop the mixed solution B into the mixed solution C, stir magnetically for 10 min, stand at room temperature for 24 h, vacuum filter, collect the purple precipitate, then wash it alternately with deionized water and anhydrous ethanol for 3 times, and vacuum dry it at 60 ° C for 12 h to obtain a purple precursor, recorded as BC / CoZn-MOF-2:1;
[0095] Step 5, according to the mass ratio of 1:4, BC / CoZn-MOF-2:1 and sulfur powder are placed at both ends of the magnetic boat respectively, and the magnetic boat is placed in a tube furnace. Under Ar atmosphere, the temperature is first increased from room temperature to 300°C at a heating rate of 5°C / min, and the temperature is kept for 2 hours, and then the temperature is increased to 700°C at a heating rate of 2°C / min, and the temperature is kept for 3 hours. The carbon nanofiber-supported cobalt zinc sulfide composite material is obtained, which is recorded as CNF / CoZn-S-2:1;
[0096] Step 6. According to the mass ratio of 8:1:1, weigh CNF / CoZn-S-2:1, acetylene black and PVDF, mix and grind them evenly, add 10 drops of N-methylpyrrolidone NMP to prepare a uniform slurry, evenly coat the slurry on the surface of a commercial polypropylene separator, and dry it to obtain a CNF / CoZn-S-2:1 modified lithium-sulfur battery separator.
[0097] Example 9
[0098] Step 1, mixing bacterial cellulose hydrogel BC with a solid content of 0.8% and deionized water in a volume ratio of 1:30, stirring evenly, and freeze-drying to obtain BC fibers with a network structure;
[0099] Step 2: Mix 0.01 mol of Co(NO3)2·6H2O and 0.005 mol of Zn(NO3)2·6H2O to obtain a mixture A, and dissolve the mixture A and 0.4 g of BC fiber in 80 mL of methanol to obtain a mixed solution B;
[0100] Step 3, dissolving 3.08 g of 2-methylimidazole in 80 mL of methanol to obtain a mixed solution C;
[0101] Step 4, drop the mixed solution B into the mixed solution C, stir magnetically for 10 min, stand at room temperature for 24 h, vacuum filter, collect the purple precipitate, then wash it alternately with deionized water and anhydrous ethanol for 3 times, and vacuum dry it at 60 ° C for 12 h to obtain a purple precursor, recorded as BC / CoZn-MOF-2:1;
[0102] Step 5, according to the mass ratio of 1:4, BC / CoZn-MOF-2:1 and sulfur powder are placed at both ends of the magnetic boat respectively, and the magnetic boat is placed in a tube furnace. Under Ar atmosphere, the temperature is first increased from room temperature to 300°C at a heating rate of 5°C / min, and the temperature is kept for 2h, and then the temperature is increased to 700°C at a heating rate of 2°C / min, and the temperature is kept for 0h, and the mixture is naturally cooled to room temperature to obtain a carbon nanofiber-supported cobalt zinc sulfide composite material, which is recorded as CNF / CoZn-S-2:1;
[0103] Step 6. According to the mass ratio of 8:1:1, weigh CNF / CoZn-S-2:1, acetylene black and PVDF, mix and grind them evenly, add 10 drops of N-methylpyrrolidone NMP to prepare a uniform slurry, evenly coat the slurry on the surface of a commercial polypropylene separator, and dry it to obtain a CNF / CoZn-S-2:1 modified lithium-sulfur battery separator.
[0104] Comparative Example 1
[0105] Step 1, mixing bacterial cellulose hydrogel BC with a solid content of 0.8% and deionized water in a volume ratio of 1:30, stirring evenly, and freeze-drying to obtain BC fibers with a network structure;
[0106] Step 2: Dissolve 0.015 mol of Co(NO3)2·6H2O and 0.15 g of BC fiber in 100 mL of methanol to obtain a mixed solution B;
[0107] Step 3, dissolving 3.08 g of 2-methylimidazole in 100 mL of methanol to obtain a mixed solution C;
[0108] Step 4, drop the mixed solution B into the mixed solution C, stir magnetically for 10 min, stand at room temperature for 24 h, vacuum filter, collect the precipitate, then wash it alternately with deionized water and anhydrous ethanol for 3 times, and vacuum dry it at 60 ° C for 12 h to obtain a precursor, recorded as BC / Co-MOF;
[0109] Step 5, according to the mass ratio of 1:4, BC / Co-MOF and sulfur powder are placed at both ends of the magnetic boat respectively, and the magnetic boat is placed in a tubular furnace. Under Ar atmosphere, the temperature is first increased from room temperature to 300°C at a heating rate of 5°C / min, and kept at this temperature for 2 hours, and then increased to 700°C at a heating rate of 2°C / min, and kept at this temperature for 2 hours, and naturally cooled to room temperature to obtain a carbon nanofiber-supported cobalt sulfide composite material, recorded as CNF / Co-S;
[0110] Step 6. According to the mass ratio of 8:1:1, weigh CNF / Co-S, acetylene black and PVDF, mix them evenly and grind them, add 10 drops of N-methylpyrrolidone NMP to prepare a uniform slurry, evenly coat the slurry on the surface of a commercial polypropylene separator, and dry it to obtain a CNF / Co-S modified lithium-sulfur battery separator.
[0111] Comparative Example 2
[0112] Step 1, mixing bacterial cellulose hydrogel BC with a solid content of 0.8% and deionized water in a volume ratio of 1:30, stirring evenly, and freeze-drying to obtain BC fibers with a network structure;
[0113] Step 2: Dissolve 0.015 mol of Zn(NO3)2·6H2O and 0.15 g of BC fiber in 100 mL of methanol to obtain a mixed solution B;
[0114] Step 3, dissolving 3.08 g of 2-methylimidazole in 100 mL of methanol to obtain a mixed solution C;
[0115] Step 4, drop the mixed solution B into the mixed solution C, stir magnetically for 10 min, stand at room temperature for 24 h, vacuum filter, collect the precipitate, then wash it alternately with deionized water and anhydrous ethanol for 3 times, and vacuum dry it at 60°C for 12 h to obtain a precursor, recorded as BC / Zn-MOF;
[0116] Step 5, according to the mass ratio of 1:4, BC / Zn-MOF and sulfur powder are placed at both ends of the magnetic boat respectively, and the magnetic boat is placed in a tubular furnace. Under Ar atmosphere, the temperature is first increased from room temperature to 300°C at a heating rate of 5°C / min, and kept at this temperature for 2 hours, and then increased to 700°C at a heating rate of 2°C / min, and kept at this temperature for 2 hours, and naturally cooled to room temperature to obtain a carbon nanofiber-supported zinc sulfide composite material, recorded as CNF / Zn-S;
[0117] Step 6. According to the mass ratio of 8:1:1, weigh CNF / Zn-S, acetylene black and PVDF, mix and grind them evenly, add 10 drops of N-methylpyrrolidone NMP to prepare a uniform slurry, evenly coat the slurry on the surface of a commercial polypropylene separator, and dry it to obtain a CNF / Zn-S modified lithium-sulfur battery separator.
[0118] like Figure 1 As shown, the pure phase CNF / Zn-S prepared in Comparative Example 2 shows typical diffraction peaks at 28.5°, 47.7° and 56.6°, which has a high degree of matching with the peak position of the standard card ZnS (PDF#39-1363); while the diffraction peaks of the pure phase CNF / Co-S prepared in Comparative Example 1 are consistent with the standard card Co4S3 (PDF#2-1458); the diffraction peaks of CNF / CoZn-S-1:1, CNF / CoZn-S-1:2 and CNF / CoZn-S-2:1 prepared in Examples 1 to 3 are mixed phases of ZnS and Co4S3, that is, ZnS and Co4S3 in CNF / The diffraction peaks of CNF / CoZn-S and ZnS coexist in the composite material, and the diffraction peaks are sharp and narrow, indicating that the cobalt-zinc sulfide supported on the carbon nanofibers prepared by the in-situ growth method and one-step vulcanization is stable in phase, has good crystallinity and high purity; in addition, it is worth noting that the diffraction peaks in CNF / CoZn-S-1:2 and CNF / CoZn-S-1:1 have a high degree of match with the standard card Co4S3 (PDF#2-1338), which show typical characteristic peaks at 31.2°, 36.1°, and 47.5°. As the molar ratio of the cobalt source / zinc source gradually increases, that is, the intensity of the Co4S3 peak in CNF / CoZn-S-2:1 increases, and the intensity of the ZnS peak remains unchanged.
[0119] from Figure 2It can be seen that in the BC / CoZn-MOF-1:2 prepared in Example 2, the CoZn-MOF particles are evenly anchored on the surface of the three-dimensional BC network, the morphology and structure are well maintained, and the in situ growth makes the CoZn-MOF particles and the BC network tightly combined, and the structure is relatively stable. In addition, it also shows that during the in situ growth process, the structure of the BC network is not significantly damaged or deformed, and the good conductivity, mechanical properties and chemical stability of the BC network can be maintained.
[0120] from Figure 3 It can be seen that after high-temperature one-step sulfurization and carbonization treatment, CNF still retains the BC network structure, and the CoZn-S particles are still evenly distributed on CNF, showing a particle morphology, without falling off or agglomeration, which is conducive to exposing more active sites. At the same time, CNF, as a highly conductive network, can not only accelerate the transfer of charges, but also has a physical restriction effect on LiPSs.
[0121] Using MWCNTs / S as the positive electrode, metallic lithium as the negative electrode, and 1.0M LiTFSI in DME:DOL=1:1Vol%with 1.0%LiNO3 solution as the electrolyte, the modified diaphragms synthesized in Examples 1 to 3, Comparative Examples 1 and 2, and the commercial polypropylene diaphragm were used as diaphragms, and Li-S batteries with 6 different diaphragms were assembled in a glove box filled with argon gas, and electrochemical performance tests were performed. The results are as follows:
[0122] like Figure 4 As shown in the figure, at a current density of 0.1C, the first cycle discharge specific capacities of Li-S batteries assembled from CNF / CoZn-S-1:1 modified lithium-sulfur battery separator, CNF / CoZn-S-1:2 modified lithium-sulfur battery separator, CNF / CoZn-S-2:1 modified lithium-sulfur battery separator, CNF / Zn-S modified lithium-sulfur battery separator, CNF / Co-S modified lithium-sulfur battery separator and commercial polypropylene separator were 1395.2 mAh g -1 、1422.8mAh·g -1 、1278.0mAh·g -1 , 1200.1mAh·g -1 、1101.2mAh·g -1 and 935.3mAh·g -1It can be seen that the discharge specific capacity of the Li-S battery assembled by the commercial polypropylene diaphragm, the CNF / Zn-S modified lithium-sulfur battery diaphragm synthesized in Comparative Example 2 and Comparative Example 1, and the CNF / Co-S modified lithium-sulfur battery diaphragm is significantly lower than the discharge specific capacity of the CNF / CoZn-S modified lithium-sulfur battery diaphragm synthesized in Examples 1 to 3, and the discharge specific capacity of the Li-S battery assembled by the CNF / CoZn-S-1:2 modified lithium-sulfur battery diaphragm synthesized in Example 2 is the highest.
[0123] from Figure 5 It can be seen that the Li-S battery assembled with the CNF / CoZn-S-1:2 modified lithium-sulfur battery separator synthesized in Example 2 has the highest specific capacity compared with the other five Li-S batteries. At current densities of 0.1C, 0.2C, 0.5C, 1C and 2C, the first cycle discharge specific capacity is 1422.8 mAh g -1 、1122.2mAh·g -1 、959.5mAh·g -1 、860.3mAh·g -1 and 770.3mAh·g -1 When the current density returns to 0.2C, the specific capacity can return to 950.2mAh g -1 , which indicates that the Li-S battery assembled with CNF / CoZn-S-1:2 modified separator has excellent reaction reversibility.
[0124] from Figure 6 It can be seen that the Li-S battery assembled with the CNF / CoZn-S-1:2 modified lithium-sulfur battery separator synthesized in Example 2 has the highest response current and the smallest potential difference in the CV curve compared with the other five Li-S batteries, which indicates that it has smaller polarization and faster redox reaction kinetics.
[0125] from Figure 7 It can be seen that the Li-S battery assembled with the CNF / CoZn-S-1:2 modified lithium-sulfur battery separator synthesized in Example 2 still maintains a specific capacity of 1046.3 mAh g after 200 cycles at a current density of 0.2C. -1 The average capacity decay rate of CNF / CoZn-S-1:2 per cycle is only 0.033%; Figure 8 It can be seen that the Li-S battery assembled with the CNF / CoZn-S-1:2 modified lithium-sulfur battery separator synthesized in Example 2 maintained 812.0 mAh g after 200 cycles at a current density of 1 C. -1 Ultra-high specific capacity; Fig. 9It can be seen that the Li-S battery assembled with the CNF / CoZn-S-1:2 modified lithium-sulfur battery separator synthesized in Example 2 still has a capacity of 709.0 mAh g after 500 cycles at a current density of 2C. -1 The specific capacity of CNF / CoZn-S-1:2 modified lithium-sulfur battery separator has an average decay rate of only 0.018%. The above shows that the Li-S battery assembled with CNF / CoZn-S-1:2 modified lithium-sulfur battery separator has excellent cycle stability, which is attributed to its stable structure, high specific surface area, abundant mesopores and many exposed active sites, which fully exerts the physical restriction and chemical adsorption of polysulfides, reduces the loss of sulfur in long cycles, and improves the actual specific capacity of the battery.
[0126] In addition, from Figure 7 to Figure 9 It can be seen that although the specific capacity and cycle stability of the Li-S battery assembled with the CNF / CoZn-S-1:1 modified lithium-sulfur battery separator prepared in Example 1 and the CNF / CoZn-S-2:1 modified lithium-sulfur battery separator prepared in Example 3 are not as good as the specific capacity and cycle stability of the Li-S battery assembled with the CNF / CoZn-S-1:2 modified lithium-sulfur battery separator synthesized in Example 2, compared with the Li-S battery assembled with the CNF / Co-S modified lithium-sulfur battery separator prepared in Comparative Example 1, the CNF / Zn-S modified lithium-sulfur battery separator prepared in Comparative Example 2 and the commercial polypropylene separator, it still shows a higher specific capacity and excellent cycle stability, indicating that CNF / CoZn-S can fully adsorb polysulfides and improve the electrochemical performance of the battery.
[0127] from Fig.10 It can be seen that the Li-S battery assembled with the CNF / CoZn-S-1:2 modified lithium-sulfur battery separator synthesized in Example 2 has the lowest Rct value, with an impedance value of 19.6Ω, which is much lower than the impedance value of 66.5Ω of the Li-S battery assembled with the commercial polypropylene separator; this indicates that the CNF / CoZn-S-1:2 modified lithium-sulfur battery separator has the smallest electron and ion transfer resistance, reduces the membrane interface impedance, thereby enhancing the redox reaction kinetics of the battery and significantly improving the electrochemical performance of the battery; in addition, the impedance values of the Li-S battery assembled with the CNF / CoZn-S-1:1 modified lithium-sulfur battery separator prepared in Example and the CNF / CoZn-S-2:1 modified lithium-sulfur battery separator prepared in Example 3 are also significantly lower than the impedances of the other three batteries, which is attributed to the fact that the carbon nanofiber-loaded cobalt-zinc sulfide composite material CNF / CoZn-S can effectively limit the "shuttle effect" of polysulfides through physical and chemical synergy, thereby effectively improving the electrochemical performance of the Li-S battery.
Claims
1. A method for preparing a carbon nanofiber-supported cobalt-zinc sulfide composite material, characterized in that: The steps include: Step 1, mixing bacterial cellulose hydrogel BC with deionized water, stirring evenly, and freeze-drying to obtain BC fibers with a network structure; Step 2, firstly mix Co(NO3)2·6H2O and Zn(NO3)2·6H2O in a molar ratio of (1-2):(1-2) to obtain a mixture A, and then dissolve 0.015 mol of the mixture A and 0.1-0.4 g of BC fiber in 50-120 mL of methanol to obtain a mixed solution B; Step 3, dissolving 3.08 g of 2-methylimidazole in 50-120 mL of methanol to obtain a mixed solution C; Step 4, drop the mixed solution B into the mixed solution C, stir, stand at room temperature, vacuum filter, wash and vacuum dry in sequence to obtain a purple BC / CoZn-MOF precursor; Step 5. According to the mass ratio of 1:4, the BC / CoZn-MOF precursor and sulfur powder are placed at both ends of the magnetic boat respectively, and the magnetic boat is placed in a tubular furnace. Under Ar atmosphere, the temperature is first increased from room temperature to 300°C at a heating rate of 5°C / min, and kept warm for 2 to 4 hours. Then, the temperature is increased to 700°C at a heating rate of 2°C / min, and kept warm for 0 to 4 hours. Naturally cool to room temperature to obtain a carbon nanofiber-loaded cobalt zinc sulfide composite material CNF / CoZn-S.
2. The method for preparing the carbon nanofiber-supported cobalt-zinc sulfide composite material according to claim 1, characterized in that: In the step 1, the volume ratio of the bacterial cellulose hydrogel BC to deionized water is 1:30, and the solid content of the bacterial cellulose hydrogel BC is 0.8%.
3. The method for preparing the carbon nanofiber-supported cobalt-zinc sulfide composite material according to claim 1, characterized in that: In step 2, the molar ratio of Co(NO3)2·6H2O to Zn(NO3)2·6H2O is 1:1, 2:1 or 1:
2.
4. The method for preparing the carbon nanofiber-supported cobalt-zinc sulfide composite material according to claim 3, characterized in that: In step 2, the molar ratio of Co(NO3)2·6H2O to Zn(NO3)2·6H2O is 1:
2.
5. The method for preparing the carbon nanofiber-supported cobalt-zinc sulfide composite material according to claim 1, characterized in that: The standing time of step 4 is 24h.
6. The method for preparing the carbon nanofiber-supported cobalt-zinc sulfide composite material according to claim 1, characterized in that: The cleaning in step 4 is performed by alternately cleaning with deionized water and anhydrous ethanol for 3 times.
7. The method for preparing the carbon nanofiber-supported cobalt-zinc sulfide composite material according to claim 1, characterized in that: The vacuum drying in step 4 is carried out at 60° C. for 12 h.
8. A carbon nanofiber-supported cobalt zinc sulfide composite material CNF / CoZn-S prepared by the method according to claim 1.
9. A modified lithium-sulfur battery separator, characterized in that: It comprises a commercial polypropylene diaphragm, the surface of which is coated with the carbon nanofiber-loaded cobalt zinc sulfide composite material CNF / CoZn-S as claimed in claim 8.
10. The modified lithium-sulfur battery separator according to claim 9, characterized in that: Prepared by the following method: CNF / CoZn-S, acetylene black and PVDF were weighed in a mass ratio of 8:1:1, mixed evenly and ground, and NMP was added to prepare a uniform slurry. The slurry was evenly coated on the surface of a commercial polypropylene separator and dried to obtain a modified lithium-sulfur battery separator.